Open string field theory with stubs - Martin Schnabl; Georg Stettinger (Journal of High Energy Physics, 2023)
Abstract There are various reasons why adding stubs to the vertices of open string field theory (OSFT) is interesting: the stubs can not only tame certain singularities and make the theory more well-behaved, but also the new theory shares a lot of similarities with closed string field theory, which helps to improve our understanding of its structure and possible solutions. In this paper we explore two natural ways of implementing stubs into the framework of OSFT, resulting in an A ∞ -algebra giving rise to infinitely many vertices. We find two distinct consistent actions, both generated by a field redefinition, interestingly sharing the same equations of motion. In the last section we illustrate their relationship and physical meaning by applying our construction to nearly marginal solutions.